Expression of Two Glutathione S-Transferase Genes in the Yeast Issatchenkia orientalis Is Induced by o-Dinitrobenzene during Cell Growth Arrest - Tamaki, Hisanori (American Society for Microbiology, 1999)
Glutathione S-transferases (GSTs) Y-1 and Y-2 from the yeast Issatchenkia orientalis were purified by passage through a glutathione-agarose column, and the cDNA for GST Y-1 was cloned and sequenced. The deduced amino acid sequence consisted of 188 residues with a total calculated molecular mass of 21,001 Da and showed 36.7% identity to that of GST Y-2, another GST isoenzyme expressed in this strain. Escherichia coli DH5α transformed with pUC119 harboring the GST Y-1 gene under the control of the lac promoter exhibited 29-fold-higher GST activity than the same strain with pUC119. Northern blot analysis revealed that both genes were highly expressed in cells cultured in the presence of 200 μM o-dinitrobenzene (DNB), one of the substrates of GST, while only the GST Y-1 gene was expressed, and only slightly, under normal (DNB-free) culture conditions. The DNB in the medium arrested cell growth until it was reduced by conjugation with reduced glutathione. Kinetic analysis of GST gene expression during detoxification of DNB revealed that the levels of expression of both genes were elevated within 3 h after the addition of DNB and that they further increased until 12 h postaddition. The levels of expression of both genes were decreased markedly when the DNB concentration in the culture medium was lowered. These results suggest that I. orientalis cells sense xenobiotics and arrest cell growth as a mechanism for preventing the induction of mutations by these compounds, while the levels of expression of the GST genes are up-regulated for detoxification.